Analisis Sentimen terhadap Kebijakan Pengembalian Penjurusan di Sekolah Menengah Atas Menggunakan Algoritma Random Forest - Saire Fernando; Mulyono; Ari Hendarno; Ersa Resita; Carli Apriansyah Hutagalung (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2026)
In the 2025/2026 academic year, the Minister of Education, Culture, Research, and Technology (Permendikbudristek) planned to reinstate majors in high schools. This policy quickly sparked public debate, generating a variety of responses from the public, particularly on YouTube. This study was conducted to analyze public sentiment towards this policy using the Random Forest algorithm. Data was obtained through YouTube comment collection between April 2025 and June 2025, which yielded 4,181 comments. The analysis showed that YouTube comments on videos regarding the policy of reinstating majors in the high school curriculum had a more positive response than negative, with a ratio of 18.3% compared to 5%, with a total of 76.7% neutral. The model's performance in classifying sentiment achieved an overall accuracy of 83.16%, with a precision of 77.56%, indicating a fairly reliable model prediction. However, recall was at 57.25%, indicating that the model still had difficulty detecting all data in small classes such as positive and negative. Overall, the model's performance is represented by an F1-score of 61.26%. This research is expected to serve as a consideration for education leaders or the Minister of Education, Culture, Research, and Technology in determining whether a policy needs to be enacted or changed.